Happy never after - Trocheck, Kathy Hogan, 1954- (HarperCollins, 1995)
Callahan agrees to locate the missing member of the popular '60s girl group, the VelvetTeens, and she doesn't have to search long. Deloras Carter, the a.w.o.l. singer, is found passed out drunk by a swimming pool near the dead body of the trio's former producer. The smoking gun in Deloras's hand suggests that the VelvetTeens won't be reuniting for a comeback tour anytime in the near future ... unless Callahan and her "Mice" can spotlight -- and survive -- a different killer act.